Lexical and Grammatical Cohesion in the Regional Regulation Discourse of West Sumatra Province - Delfia, Elly; Wijana, I Dewa Putu; Jati Kesuma, Tri Mastoyo (Journal of Language and Literature, 2023)
This study aims to explain the discourse structure, specifically the lexical and grammatical cohesion in the discourse of West Sumatra Province, with a discourse analysis approach. The object of this research is a special regional regulation (SRR) of West Sumatra Province, which is different from Regional Regulation (RR) in other regions in Indonesia, as evident in the use of local concepts and terms. This regulation is interesting to study in cohesion because its structures represent the social reality of the indigenous people’s lives. One notable regulation is Nagari, the lowest government level in West Sumatra Province, with authority to regulate their communities and customary land in the Republic of Indonesia. That social reality is illustrated in the cohesiveness and harmony of the relationships of the forms that construct the discourse. This mixed-method research employs both quantitative and qualitative data and applied lexical and grammatical cohesion theory in data analysis. Findings show that lexical cohesion is realized in the following forms: repetition, synonym, meronymy, hyponym, and collocation; while grammatical cohesion is realized in the form of references, substitutions, and conjunctions. Based on the analysis, lexical and grammatical cohesion are interconnected constituents in building the integrity of the discourse structure in the SRR of West Sumatra Province. Cohesion plays a role in determining the meaning of the discourse as a whole and reflects the coherence of ideational meanings in discourse.